Life Cycle and Sustainability of Abrasive Tools - LINKE, BARBARA (RWTHedition,, 2016)
This monograph focuses on abrasive tools for grinding, polishing, honing, and lapping operations. The book describes the life cycle of abrasive tools from raw material processing of abrasive grits and bonding, manufacturing of monolithic or multi-layered tools, tool use to tool end-of-life. Moreover, this work highlights sustainability challenges including economic, environmental, social and technological aspects. The target audience primarily comprises research and industry experts in the field of manufacturing, but the book may also be beneficial for graduate students.